METHODS OF TEACHING 3-4 YEAR OLD CHILDREN THROUGH DIDACTIC GAMES (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes unconventional and interactive methods and methods of teaching 3-4-year-old children through didactic games, the essence of such games, the use of didactic games in the pedagogical process, and the importance of children's mental development.  the possibilities of applying modern knowledge and pre-school education activities are analyzed.